2020
DOI: 10.1177/0890334420964070
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Prescribing Process of Domperidone for Low Milk Supply: A Qualitative Study Among Mothers, IBCLCs, and Family Doctors

Abstract: Background When mothers are confronted with milk supply problems, taking domperidone is regularly suggested. However, domperidone has been associated with sudden cardiac death and caution in prescribing is advised. In 2016, a multidisciplinary group of authors from a tertiary academic hospital (Erasmus MC) published a clinical protocol in a leading Dutch physicians’ journal to support Dutch family physicians in prescribing domperidone to stimulate lactation. Research aim To explore consumer and health care pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This suggests either a communication gap between recommendations/information about galactagogues like domperidone that misinforms practices of use, inconsistency around how the risk is presented or explained, and, a moral burden on women which upholds practices that may be risky to themselves as unimportant vis-à-vis their responsibility to baby. Few women in our study reported active discussions with prescribers regarding potential risks of domperidone use, representing a similar finding to that of Tauritz Bakker et al [28].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This suggests either a communication gap between recommendations/information about galactagogues like domperidone that misinforms practices of use, inconsistency around how the risk is presented or explained, and, a moral burden on women which upholds practices that may be risky to themselves as unimportant vis-à-vis their responsibility to baby. Few women in our study reported active discussions with prescribers regarding potential risks of domperidone use, representing a similar finding to that of Tauritz Bakker et al [28].…”
Section: Discussionsupporting
confidence: 88%
“…The issues around practices of use that involve selfmanaged dosing and long-term use was also observed in interviews conducted by Tauritz Bakker et al with women who took domperidone for lactation insufficiency in the Netherlands [28]. Such practices may be influenced by the lack of agreement by healthcare practitioners around the criteria for use, including no consensus on the safest and optimal dosing and the duration of use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations